A new criterion for close-to-convexity of partial sums of certain hypergeometric functions. (1997) - Jahangiri, Massoud
Abstract : We consider the partial sums of certain hypergeometric functions and establish conditions imposed on the locations of zeros of those polynomials in order to be close-to-convex in the open unit disk.